Dynamic Market Processes and the Rewards to Up-To-Date Information: Discussion - Tepper, Irwin (Journal of Finance, 1977)
Irwin Tepper, Dynamic Market Processes and the Rewards to Up-To-Date Information: Discussion, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), p. 306